2015
DOI: 10.3109/03009742.2014.999351
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight in children and adolescents with juvenile idiopathic arthritis

Abstract: The prevalence of overweight in JIA was comparable to the general population and decreased significantly over time. The decrease was associated with higher functional ability and JIA patients should be encouraged to be more physically active. The role of an elevated body mass index (BMI) in the long-term outcome of JIA needs to be addressed in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 38 publications
4
13
1
3
Order By: Relevance
“…The higher body weight of patients with JIA and T1D resulted in higher BMI SDS. A previous NPRD analysis of BMI in patients with JIA compared with population-based data in Germany did not reveal significant differences in general, 21 but the study showed an increased prevalence of a higher BMI in patients with systemic JIA and enthesitis-related arthritis. These categories are not distributed differently between patients with JIA with and without T1D; thus, the underlying cause for a higher BMI might be related to T1Dindicated insulin therapy, which is associated with weight gain.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The higher body weight of patients with JIA and T1D resulted in higher BMI SDS. A previous NPRD analysis of BMI in patients with JIA compared with population-based data in Germany did not reveal significant differences in general, 21 but the study showed an increased prevalence of a higher BMI in patients with systemic JIA and enthesitis-related arthritis. These categories are not distributed differently between patients with JIA with and without T1D; thus, the underlying cause for a higher BMI might be related to T1Dindicated insulin therapy, which is associated with weight gain.…”
Section: Discussioncontrasting
confidence: 52%
“…For more details, we refer to previous NPRD publications. [20][21][22] Patients with JIA according to the International League of Associations for Rheumatology criteria 23,24 who were 20 years of age or younger and recorded in the NPRD between 2012 and 2014, were included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…In line with this theory, our study revealed that higher BMI is a risk factor for developing enthesitis. Schenck et al showed recently in a large national German pediatric rheumatology database that those with ERA and systemic arthritis had the highest prevalence of overweight and obesity among juvenile idiopathic arthritis patients. Indeed, in a study of ultrasound to determine whether the Madrid Enthesitis Index could identify patients with psoriasis destined to develop PsA, results showed that in patients with a high BMI (>30) there was no difference between patients with PsA, patients with psoriasis alone, or healthy controls .…”
Section: Discussionmentioning
confidence: 99%
“…In dieser relativ kleinen Studienpopulation ließen sich keine Zusammenhänge zwischen Fettleibigkeit und klinischer Krankheitsaktivität, Krankheitsdauer oder Medikation feststellen. Ein ähnliches Verhältnis zur Normalbevölkerung -wenn auch auf einem deutlich niedrigerem Niveau -zeigte sich für JIA-Patienten im Rahmen der "Kerndokumentation rheumakranker Kinder und Jugendlicher" (DRFZ) [53].…”
Section: Adipositasunclassified